STUDY OF INSTRUCTIONAL MODELS AND SYNTAX AS AN EFFORT FOR DEVELOPING ‘OIDDE’ INSTRUCTIONAL MODEL - Atok Miftachul Hudha; Mohamad Amin; Sutiman Bambang; Sa'dun Akbar (University of Muhammadiyah Malang, 2016)
The 21st century requires the availability of human resources with seven skills or competence (Maftuh, 2016), namely: 1) critical thinking and problem solving skills, 2) creative and innovative, 3) behave ethically, 4) flexible and quick to adapt, 5) competence in ICT and literacy, 6) interpersonal and collaborative capabilities, 7) social skills and cross-cultural interaction. One of the competence of human resources of the 21st century are behaving ethically should be established and developed through learning that includes the study of ethics because ethical behavior can not be created and owned as it is by human, but must proceed through solving problem, especially ethical dilemma solving on the ethical problems atau problematics of ethics.The fundamental problem, in order to ethical behavior competence can be achieved through learning, is the right model of learning is not found yet by teachers to implement the learning associated with ethical values as expected in character education (Hudha, et al, 2014a, 2014b, 2014c). Therefore, it needs a decent learning model (valid), practical and effective so that ethics learning, to establish a human resources behave ethically, can be met.Thus, it is necessary to study (to analyze) and modificate the steps of learning (syntax) existing learning model, in order to obtain the results of the development model of learning syntax. One model of learning that is feasible, practical, and effective question is the learning model on the analysis and modification of syntax model of social learning, syntax learning model systems behavior (Joyce and Weil, 1980, Joyce, et al, 2009) as well as syntax learning model Tri Prakoro (Akbar, 2013). The modified syntax generate learning model 'OIDDE' which is an acronym of orientation, identify, discussion, decision, and engage in behavior. Keywords: Ethics, OIDDE Learning Model, Model Behavior Learning System-consistent, Social Learning Model, Model Learning Triprakoro, Syntax